Women's Perceived Barriers to Accessing Post-Abortion Care Services in Selected Districts in KwaZulu Natal Province, South Africa: A Qualitative Study - M. Netshinombelo; M. S. Maputle; D. U. Ramathuba (Ubiquity Press, 2022)
Background: Despite different interventions to curb unwanted pregnancies, repositioning Family Planning and post-abortion care services as critical priorities in health programme in Kwa-Zulu Natal, women are still admitted with induced abortion complications. Aim: The aim was to explore challenges experienced by women who are accessing post-abortion care services at selected public hospitals. Methods: A qualitative explorative, descriptive, and contextual approach was used. The population comprised all women who presented with incomplete abortion and had accessed PAC services in the selected hospitals. Purposive convenience sampling was used to select the 23 participants. Data were collected through in-depth interviews with all participants on discharge and analysed through open-coding method. Trustworthiness was ensured, by considering the criteria of credibility, dependability, applicability, and transferability. Ethical considerations were secured by requesting consent and permission to conduct the study. All interviews were voluntarily conducted following the ethically approved informed consent, anonymity and confidentiality were maintained. Findings: Three themes emerged reflecting challenges from women's perspectives on accessing post abortion care. These themes were: transportation barriers, stigma, and mistreatment (lack of analgesics, early discharge). Conclusion: Conclusion showed the description of perceived barriers and experiences related to accessing, seeking and care received during the process of PAC. Inaccessibility to PAC was due to poor road, poor mode, lack of transport and long distance from the community to the hospital, long waiting queues, stigma, and discrimination. The PAC services should be accessible with the increased number of facilities and adequately trained staff with functional equipment and guidelines. Value clarification workshops for health professionals are essential.